Micro-Affiliate Persuasion Strategies in Banjar Cultural Communication within TikTok Affiliate Ecosystem in South Kalimantan - Noviana Sari (Jogjakarta Communication Conference (JCC), 2026)
The development of the creator economy on social media has given rise to new digital marketing practices through the TikTok Affiliate program, where creators act as intermediaries for product promotion while earning commissions from sales. In practice, micro-affiliates rely not only on commercial promotional strategies but also utilize personal, cultural, and affective communication approaches to build rapport with their audiences. This study aims to analyze how micro-affiliate persuasion strategies are constructed within Banjar cultural communication within the TikTok Affiliate ecosystem in South Kalimantan. This study used a qualitative approach with content analysis of TikTok video content produced by five micro-affiliate creators actively promoting skincare products. Data were collected through observation of video content, digital documentation, and categorization of communication elements that emerged within the content, such as narrative form, use of local language, visual representation of the body, affective performance, and purchase strategies. The results indicate that the persuasive strategies used by micro-affiliates are formed through three main patterns. First, relational persuasion, manifested through narratives of personal experiences and the use of Banjarese language to create cultural rapport with the audience. Second, demonstrative persuasion, which involves using the creator's body as a visual medium to demonstrate the use and effectiveness of skincare products. Third, implicit economic persuasion, which displays pricing information or promotions without a direct call to purchase. The findings of this study indicate that micro-affiliates function not only as digital marketing agents but also as mediators of cultural communication, connecting digital consumption practices with local identities. Thus, TikTok Affiliate practices are not merely platform economic activities but also a communication process involving the production of cultural meaning within the social media space.